2017
DOI: 10.1038/mp.2017.39
|View full text |Cite
|
Sign up to set email alerts
|

Ptchd1 deficiency induces excitatory synaptic and cognitive dysfunctions in mouse

Abstract: Synapse development and neuronal activity represent fundamental processes for the establishment of cognitive function. Structural organization as well as signalling pathways from receptor stimulation to gene expression regulation are mediated by synaptic activity and misregulated in neurodevelopmental disorders such as autism spectrum disorder (ASD) and intellectual disability (ID). Deleterious mutations in the PTCHD1 (Patched domain containing 1) gene have been described in male patients with X-linked ID and/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
97
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(107 citation statements)
references
References 47 publications
8
97
2
Order By: Relevance
“…The first dataset we assessed was obtained from Ptchd1 -KO mice. Loss-of-function mutations in the PTCHD1 gene lead to X-linked intellectual disability (OMIM # 300830) ( Ung et al, 2017 ). We found that nearly 23% (185 genes) of the genes that are downregulated in the hippocampus of Ptchd1 -KO mice are amongst the genes that increase following DBS in WT mice ( Figure 7A ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The first dataset we assessed was obtained from Ptchd1 -KO mice. Loss-of-function mutations in the PTCHD1 gene lead to X-linked intellectual disability (OMIM # 300830) ( Ung et al, 2017 ). We found that nearly 23% (185 genes) of the genes that are downregulated in the hippocampus of Ptchd1 -KO mice are amongst the genes that increase following DBS in WT mice ( Figure 7A ).…”
Section: Resultsmentioning
confidence: 99%
“…Limma ( Ritchie et al, 2015 ), a R package was used for differential expression analysis and genes with FDR < 0.05 and absolute logFC >0 were called as differentially expressed and were used for further analysis. For Intellectual Disorder, we used list of differentially expressed downregulated genes from the following studies ( Mehmood et al, 2011 ; Ung et al, 2017 ).…”
Section: Methodsmentioning
confidence: 99%
“…In situ hybridization and PCR analysis. In situ hybridizations with chromogenic detection were done using digoxigenin-labeled cRNA probes and were performed as described previously (Schaeren-Wiemers and Gerfin-Moser, 1993). The DNA fragment encoding the Ptchd1 probe contained SP6 and T7 promoters flanking the 5Ј-or 3Ј-end, respectively: Ptchd1:CCGCTCTGCTCTAGGATGCTGCGGCAGGTTCTGCACAGG GGCTTGAGGACGTGTTTCTCCCGGCTTGGCCACTTCATTGCCA GTCACCCGGTCTTCTTTGCTTCGGCGCCGGTGCTCATCTCCAT CCTGCTCGGCGCCAGCTTCAGCCGCTACCAGGTCGAAGAGAGC GTGGAGCACCTGCTGGCGCCCCAGCACAGCCTAGCCAAGATCG AGCGCAACCTAGTCAACAGCCTCTTCCCGGTCAACCGCTCCAAG CACCGGCTCTACTCGGACCTGCAGACCCCTGGGCGCTACGGCC GGGTCATTGTCACCTCCTACCAGAAAGCCAACATGCTAGACC AACATCACACGGACCTGA.…”
Section: Methodsmentioning
confidence: 99%
“…PTCHD1 encodes a transmembrane protein with a patched domain, and its involvement in neurodevelopmental disorders is supported by microdeletions and frameshift mutations in individuals with neurodevelopmental delay (NDD), intellectual disability, and ASD (15)(16)(17)(18)(19)(20)(21). However, recently described Ptchd1 mutant mice had impairments in attention and cognition (22)(23)(24) but did not overtly exhibit ASD-associated behaviors. Also, many ASDassociated PTCHD1 locus microdeletions are upstream of the PTCHD1 protein-coding gene and disrupt exons of the neighboring brain-enriched long noncoding RNA (lncRNA) PTCHD1-AS (15).…”
mentioning
confidence: 99%